The attractiveness of selected Central European countries for winter sports and mountain hiking - Krzesiwo, Kinga; Ziółkowska-Weiss, Kamila; Żemła, Michał (Turyzm/Tourism, 2018)
Hiking, downhill skiing and snowboarding are among the most popular forms of active tourism in mountainous areas. Their popularity and their mass scale do not only result from the presence of the appropriate landscape, but also from its appropriate development. The objective of the article is to attempt to assess the attractiveness of selected Central European countries in terms of winter sports and mountain hiking, to consider the opinions of students who live in Visegrad Group countries, as well as to evaluate the barriers to development of their competitive offers. According to respondents, the most attractive countries for winter sports are Austria and Slovakia, and the least attractive are Hungary, Romania and Lithuania. In turn, according to the students, the best conditions for mountain hiking are in Slovakia, Austria, the Czech Republic and Poland. In addition, respondents from particular countries assessed domestic offers highly.